Comunicação boca a boca: processos de transmissão e recepção - Caribé, Yuri Jivago Amorim (2007)
This paper presents an analysis of the relation technique-religion in the modern world, from the meditations of the technologies of information and communication, in a theoretical approach and a study of instance: the Associação do Senhor Jesus and the TV Século 21, from the Catholic Church. In the last decades of the twentieth century, with the increasing optimization of the computing technological sources and the diversification of its possible applications and the popularization of mass communication means, the tendency of changes in society ran freely, due to the new data set in the dynamics of relationships, material production and values. This way, the religious experience, that has always been very related to individual experience and located closed to the individual, in a deep identification with his space and time, far enough just to distinct the sacred field from profane field and different sacred fields, as well as the quotidian immanence with the temporal ritualized transcendence, broaden in the possibility of virtual and interactivity given by technological means. In the traditional way the mediation level is face-to-face. With the communication and information technologies the interaction context enlarges and then there is the possibility to change the dimensions of the categories of time and space. The time and space assume the dimension of the net of the connectivity of the instantaneously without a locus. The practical examples are the use of television, internet and telephone, in a simultaneous way, today in a lot of religious expressions